Research On The Composition And Structure Of Β -Glucans Isolated From Basidiomycete Raw Materials Inonotus Hispidus - Gulnoza Abduvakhobovna Khalilova; Abbaskhan Sabirkhanovich Turaev; Bahtiyor Ikromovich Muhitdinov; Albina Vasilevna Filatova; Saidakhon Bokijonovna Haytmetova (The American Journal of Applied Sciences, 2021)
This article highlights the conducted researches on the composition and structure of β-glucans isolated from the basidiomycete raw material Inonotus hispidus. By means of using the alditol acetate method, as well as by UV and IR methods, one-dimensional (13C NMR, 1H NMR), two-dimensional (1H-1H COSY, 1H-13C HSQC) NMR spectroscopy, the composition and molecular structure of polysaccharides were determined and their branching was proved. It was clarified that the composition of the polysaccharide fractions consists mainly of glucose residues (68-100%), as well as residues of fructose, xylose, mannose and galactose as minor monosaccharides. NMR spectroscopic studies of the specimens showed that the obtained polysaccharides consist of branched glucan structures linked by α- and β-glycosidic bonds. In the structure of β-glucans, the main chain is linked mainly through β-1,3-, partially β-1,4-glycosidic bonds, the branched parts consist of one or more β-D-glucose residues that are linked β-1,3- glycosidic bonds, as well as with the main chain, mainly through α- or β-1,6-glycosidic bonds. The results of the study of molecular parameters showed that the MW of β-glucans of basidiomycetes are in the range of 9100-9900 Da, MWD - 1.2-1.5.